Hypertrophic signaling compensates for contractile and metabolic consequences of DNA methyltransferase 3A loss in human cardiomyocytes. (May 2021) - Madsen, Alexandra; Krause, Julia; Höppner, Grit; Hirt, Marc N.; Tan, Wilson Lek Wen; Lim, Ives; Hansen, Arne; Nikolaev, Viacheslav O.; Foo, Roger S.Y.; Eschenhagen, Thomas; Stenzig, Justus
Abstract: The role of DNA methylation in cardiomyocyte physiology and cardiac disease remains a matter of controversy. We have recently provided evidence for an important role of DNMT3A in human cardiomyocyte cell homeostasis and metabolism, using engineered heart tissue (EHT) generated from human induced pluripotent stem cell (hiPSC)-derived cardiomyocytes carrying a knockout of the de novo DNA methyltransferase DNMT3A. Unlike isogenic control EHT, knockout EHT displayed morphological abnormalities such as lipid accumulations inside cardiomyocytes associated with impaired mitochondrial metabolism, as well as functional defects and impaired glucose metabolism. Here, we analyzed the role of DNMT3A in the setting of cardiac hypertrophy. We induced hypertrophic signaling by treatment with 50 nM endothelin-1 and 20 μM phenylephrine for one week and assessed EHT contractility, morphology, DNA methylation, and gene expression. While both knockout EHTs and isogenic controls showed the expected activation of the hypertrophic gene program, knockout EHTs were protected from hypertrophy-related functional impairment. Conversely, hypertrophic treatment prevented the metabolic consequences of a loss of DNMT3A, i.e. abolished lipid accumulation in cardiomyocytes likely by partial normalization of mitochondrial metabolism and restored glucose metabolism and metabolism-related gene expression of knockout EHT. Together, these data suggest an important role of DNA methylation not only for cardiomyocyte physiology, but also in the setting of cardiac disease. Graphical abstract: Unlabelled Image Highlights: Loss of DNMT3A in cardiomyocytes pathologically affects metabolism and contractility. Loss of DNMT3A attenuates cardiomyocyte functional impairment in hypertrophy. Hypertrophic signaling improves mitochondrial metabolism in the absence of DNMT3A. Hypertrophic signaling rescues glucose metabolism in DNMT3A knockout cardiomyocytes.